Intrinsic Cognitive Load in Online Learning Model of School Mathematics 1 in Covid-19 Pandemic Period - Yohanes, Barep; Yusuf, Feby Indriana (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2021)
The study aims at determining the emergence of intrinsic cognitive load in online learning models of School Mathematics 1 in Covid-19 pandemic period. This research is a descriptive qualitative one the data of which are obtained from observation sheets, questionnaires and interview results. Validity checking uses the triangulation method. The results of the study show that the intrinsic cognitive load is caused by the interactivity and isolated/interacting elements contained in the learning process. Elements of interactivity are in the form of terms or concepts in Mathematics learning. These terms or concepts, for examples, are the meaning of Knowledge, Standard Measurement, Mathematical Approach, Intertwined Principles, Content, Context, Competence, PISA Learning Concepts, De-conceptualization, Systems Approach, Conceptual Approach, etc. Isolated/interacting elements are seen from looking for examples of implementation in the real world and actualization of events in Indonesia. An example of implementation in the real world is an element that interacts in real situations in the learning practice of Mathematics.